Surface display of a manganese-binding domain enhances production and stress resistance in Bacillus subtilis spores - Nguyen, Nhi N. Y.; Truong, Tuom T. T.; Van Nguyen, Dong; Phan, Trang T. P.; Nguyen, Hoang Duc (Frontiers in Microbiology, 2025)
IntroductionBacillus subtilis spores are widely used as platforms for antigen display due to their stability and safety. However, the potential impact of surface-expressed functional proteins, such as metal-binding antigen proteins, on spore physiology remains largely unexplored. This study investigated the effects of the surface-expressed manganese-binding domain of manganese transport protein C (MntC) from Staphylococcus aureus on spore development and stress resistance.MethodsA recombinant B. subtilis strain, BsHT2380, was engineered by double cross-over integration of PcotB-cotB-mntC at the amyE locus, confirmed by PCR. MntC expression on the spore surface was verified via western blot, spore ELISA and confocal fluorescence microscopy. BsHT2380 spores exhibited increased manganese accumulation compared to controls, as measured by flame atomic absorption spectroscopy (F-AAS). EDTA treatment confirmed that the bound Mn2+ was surface-associated. Correlation between Schaeffer-Fulton staining and CFU counts indicated that Mn2+ accumulation enhanced spore production efficiency.ResultsThe BsHT2380 strain produced 71% mature spores by 48 hours, with spore levels remaining stable from 48 to 72 hours, suggesting this period represents the peak of sporulation. Importantly, BsHT2380 spores displayed enhanced resilience, with significantly higher survival rates under lysozyme (73%) and wet heat (70%) stress compared to control strains.DiscussionThese findings demonstrated that surface-expressed manganese binding domain could modulate spore physiology, improving both production and resistance, and highlight the potential of surface-displayed proteins in spore-based biotechnological applications, particularly recombinant spore-based vaccines that combine immunogenic antigen presentation with enhanced structural robustness.